Few women receive a specific explanation of a stillbirth - an online survey of women's perceptions and thoughts about the cause of their baby's death - Berit Höglund; Ingela Rådestad; Ingegerd Hildingsson (BMC, 2019)
Abstract Background In Sweden, three to four out of every 1000 pregnancies end in stillbirth each year. The aim of this study was to investigate whether women who had experienced stillbirth perceived that they had received an explanation of the death and whether they believed that healthcare professionals were responsible for the death of the baby. Methods An online survey of 356 women in Sweden who had experienced a stillbirth from January 2010 to April 2014. A mixed-methods approach with qualitative content analysis was used to examine the women's responses. Results Nearly half of the women (48.6%) reported that they had not received any explanation as to why their babies had died. Of the women who reported that they had received an explanation, 84 (23.6%) had a specific explanation, and 99 (27.8%) had a vague explanation. In total, 73 (30.0%) of the 243 women who answered the question "Do you believe that healthcare personnel were responsible for the stillbirth?" stated Yes. The women reported that the healthcare staff had not acknowledged their intuition that the pregnancy was proceeding poorly. Furthermore, they perceived that the staff met them with nonchalance and arrogance. Additionally, the midwife had ignored or normalised the symptoms that could indicate that their pregnancy was proceeding poorly. Some women added that neglect and avoidance among the healthcare staff could have led to a lack of monitoring, which could have been crucial for the outcome of the pregnancy. Conclusions Half of the women surveyed reported that they had not received an explanation of their baby's death, and more than one-fourth held healthcare professionals responsible for the death.